1995
DOI: 10.1111/j.1525-1446.1995.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Spirit of Rural Community Nursing: Documentation Burden

Abstract: Rural community and public health nursing are characterized by an impressive commitment of nurses to their communities and a connectedness of people to one another. Home care as an integral part of long-term and acute care for the older adult population has emerged as a vital practice area in community health nursing. The purpose of this ethnographic field study was to describe rural home care for frail older adults from the perspective of those providing and receiving care. More than 250 interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…Local affinity influenced the staff's actions. Staff involvement in rural contexts has been observed in other studies (Congdon & Magilvy, 1995 /2007, Ryan & McKenna, 2013 ). Ryan and McKenna ( 2013 ) found that when the older residents and staff knew each other and friends and neighbors visited, this facilitated a more positive transition for older people and their families.…”
Section: Discussionsupporting
confidence: 66%
“…Local affinity influenced the staff's actions. Staff involvement in rural contexts has been observed in other studies (Congdon & Magilvy, 1995 /2007, Ryan & McKenna, 2013 ). Ryan and McKenna ( 2013 ) found that when the older residents and staff knew each other and friends and neighbors visited, this facilitated a more positive transition for older people and their families.…”
Section: Discussionsupporting
confidence: 66%
“…Planning for nursing recruitment must be intertwined with examination of retention factors. Improvement of the job environment (Pan, Dunkin, Muus, Harris, & Geller, 1995), minimizing paperwork requirements (Congdon & Magilvy, 1995), addressing inequality of salaries (Pan & Straub, 1997), and continued professional education development (Farmer & Richardson, 1997) are workforce policy areas to be addressed. In many cases, restraints on the scope of local rural clinical care are limited as much by the availability of experienced local clinic and hospital nursing staff configurations as by the physician mix.…”
Section: Nursesmentioning
confidence: 99%
“…This is related to an interplay of personal, environmental and wider work-related factors. Professional isolation, lack of recognition limited access to professional education, high workloads and stress related to lack of replacement staff, long work hours, limited resources and sometimes unsupportive management practices are commonly described workplace challenges [3,19-22]. …”
Section: Introductionmentioning
confidence: 99%